Cloning and Heterologous Expression of Extracellular Plantaricin F Produced by Lactobacillus plantarum S34 Isolated from â€œBekasamâ€ in Lactococcus lactis (Indonesian Society for microbiology, 2016)
Plantaricin F (pln F) is bacteriocins produced by Lactobacillus plantarum are mostly applied in food to prevent microbial contamination. Biosynthesis of pln F is controlled by plantaricin A (pln A) which is primarily a peptide pheromone that controls the production of antimicrobial peptides in L. plantarum. Pre-mature pln A contains signal peptide and utilizes the general secretory pathway for export this peptide. The aim of this study was to construct a fusion of pln A signal peptide with mature pln F and to investigate the antimicrobial activity of pln F. Extracellular pln A- encoding the plnA gene were cloned into pGEM-Teasy vector to be used as a source for signal peptide SPplnA. A polymerase chain reaction (PCR) overlaps technique has been used in the construction of the fused gene with size of 171 bp while the individual gene obtained by this technique was 66 bp for pln A signal peptide and 105 bp for pln F. A gene encoding the pln A signal peptide (SPplnA) fused to mature plantaricin F, Â fused gene were then cloned into pNZ8148 as expression vector under the control of the nisin promoter (Pnis A) to generate a pNZ8148 SPplnA-plnF. Molecular expression study showed that recombinant Lactococcus lactis NZ3900 was able to express the mature pln F at transcription and translation level with size of 171 bp (by RT-PCR) and 3.8 kDa (by SDS-PAGE), respectively after 0.5-5 ng/ml nisin induction (OD600 0,5). Furthermore, the supernatants of the recombinant L. lactis NZ3900 showed antimicrobial activity against Escherichia coli ATCC 8739, Staphylococcus aureus ATCC 6539 and Listeria monocytogenes BTCC B693. Collectively, the successfulness of expression of functional pln F gene under the control of nisin induction in L. lactis NZ3900, for the first time.